Measuring anxiety related to COVID-19: Factor analysis and psychometric properties of the Arabic Coronavirus Anxiety Scale. - Zahir Vally (Public Library of Science (PLoS), 2021)
Literature reports that fear and anxiety related to the coronavirus (COVID-19) pandemic may be a significant factor in promoting adherence to health-protective behaviours. This study aimed to validate an Arabic version of the Coronavirus Anxiety Scale (CAS). Participants aged 18 to 58 years of age were recruited from a university population (students and staff) as well as via social media from 22 June to 18 July 2020 when the United Arab Emirates was under a partial government-instituted lockdown. They completed Arabic versions of the CAS and the Fear of COVID-19 Scale. A confirmatory factor analysis produced a unidimensional structure and all items satisfactorily loaded onto this single factor (i.e., the physiological symptoms of fear and anxiety related to coronavirus). The Arabic CAS was internally consistent and concurrently valid. These preliminary findings suggest that the Arabic CAS is a valid and reliable instrument to employ in the assessment of dysfunctional anxiety related to coronavirus. The availability of this validated measure will enable the further conduct of a variety of mental health studies in relation to the COVID-19 pandemic. It also holds clinical utility as a potential screening measure for those afflicted by anxiety symptomology during the pandemic.